2019
DOI: 10.1097/spv.0000000000000702
|View full text |Cite
|
Sign up to set email alerts
|

Diet Modifications in Older Women With Fecal Incontinence: A Qualitative Study

Abstract: Objective The aim of the study was to investigate dietary modification strategies used by community-dwelling older women to manage their fecal incontinence (FI). Methods We conducted a qualitative study with focus groups wherein women 65 years and older with FI shared their experiences managing the condition. We explored the following: (1) association between diet and FI symptoms, (2) dietary strategies and modifications used by older women to manage FI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Another study surveyed the self-management methods of LARS after surgery according to the relationship reported by patients in postoperative daily life, and dietary patterns of low fat and high fiber were chosen by 14.8% of patients to manage defecation dysfunction ( 26 ). In addition, fried foods and greasy foods were also reported in past studies that they were likely to worsen the fecal incontinence( 27 , 28 ). It could be seen that too much intake of oil in daily life after surgery is harmful to the management of LARS.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Another study surveyed the self-management methods of LARS after surgery according to the relationship reported by patients in postoperative daily life, and dietary patterns of low fat and high fiber were chosen by 14.8% of patients to manage defecation dysfunction ( 26 ). In addition, fried foods and greasy foods were also reported in past studies that they were likely to worsen the fecal incontinence( 27 , 28 ). It could be seen that too much intake of oil in daily life after surgery is harmful to the management of LARS.…”
Section: Discussionmentioning
confidence: 83%
“…Some other foods, such as fruits, vegetables and milk products, showed some relationship with LARS in other studies conducted in some European countries. Several studies reported that too much intake of milk products may aggravate dirrhea ( 17 , 27 , 28 ). The specific effect of vegetables and fruits on LARS were not consistent in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies suggest that geriatric and women's health providers lack training in diet analysis and diet modification which is generally considered the purview of nutritionists 9 . However, older women with FI are looking to obtain reliable diet modification advice from their health care providers 6 . We have developed a simple but structured dietary intervention that could possibly be implemented by a wide range of providers who take care of women with FI.…”
Section: Discussionmentioning
confidence: 99%
“…A conceptual framework for the dietary intervention was created using the combined results of behavioral change theory framework, a systematic review on dietary interventions for FI, 5 and findings from a previously published focus group-based study. 6 (Table 1) An advisory group with expertise in geriatrics, nutrition, urogynecology and gastroenterology was developed to provide input on the intervention and to ensure that the intervention materials were compatible with national, demographic-specific, and nutritional recommendations. The process resulted in the creation of two educational booklets entitled "Dietary Management for ABL," "Ways to Naturally Increase Dietary Fiber," and "Food and Bowel Journal" (Supplementary Appendix S1).…”
Section: Methodsmentioning
confidence: 99%
“…The prolonged, segmental, and retrograde phasic activity induced by a fat meal may delay colon transit. Thus, meal composition influences colonic motor response [8,9].…”
Section: Percentage Of Macronutrientsmentioning
confidence: 99%